REVITALISASI PASAR TRADISIONAL UNTUK PEMBERDAYAAN EKONOMI – SOSIAL KERAKYATAN: SUATU LESSON LEARNED - Biswan, Ali Tafriji; Widiastiti, Komang Andriliani (Universitas Nusantara PGRI Kediri, 2024)
This study evaluates the impact of the Pasar Banyuasri revitalization on trader performance and the challenges encountered in offering lessons for traditional market revitalization policies. Using a qualitative descriptive method, data was collected through interviews, observations, and document studies. Findings indicate that the revitalization has not fully met its objectives, with decreased trader income and empty stalls being significant issues. High retribution fees and the partially ineffective integration of the new Mall Pelayanan Publik (MPP) further impacted the revitalization outcomes. The novelty of this research lies in its in-depth analysis of the effects of traditional market revitalization and the impact of policy fees on traders, providing new insights for policy improvement and market strategies. This study offers valuable lessons for developing traditional market revitalization policies and significantly contributes to the literature on market management.